2002
DOI: 10.1097/00024382-200207000-00014
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tumor Necrosis Factor-?? on Microvascular Permeability in an Isolated, Perfused Lung

Abstract: This study examines the hypotheses that TNF-alpha causes a dose-dependent increase in the microvascular permeability of ex vivo buffer perfused lungs that is quantitatively similar to that caused by lipopolysaccharide (LPS) or thromboxane A2 (TxA2). We also postulated that TNF-alpha potentiates the effect of interleukin-1beta (IL-1beta) or TxA2 receptor activation on pulmonary microvascular permeability. Lungs harvested from Wistar rats were perfused ex vivo with Krebs-Henseleit buffer containing 0, 10, 100, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
5
10
0
Order By: Relevance
“…In the present study, subcutaneous administration of ONO-1301 significantly attenuated bleomycin-induced increases in total cell counts, neutrophil counts, and total protein level in BAL fluid. Earlier studies have shown that TXA 2 acts as a proinflammatory mediator via enhancement of pulmonary vascular permeability (18,24) and neutrophil adhesion (33). In the present study, TXB 2 , a stable metabolite of TXA 2 , was significantly increased after bleomycin injection, which is consistent with previous studies (2, 8).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, subcutaneous administration of ONO-1301 significantly attenuated bleomycin-induced increases in total cell counts, neutrophil counts, and total protein level in BAL fluid. Earlier studies have shown that TXA 2 acts as a proinflammatory mediator via enhancement of pulmonary vascular permeability (18,24) and neutrophil adhesion (33). In the present study, TXB 2 , a stable metabolite of TXA 2 , was significantly increased after bleomycin injection, which is consistent with previous studies (2, 8).…”
Section: Discussionsupporting
confidence: 93%
“…Prostacyclin inhibits migration, proliferation, and collagen synthesis in fibroblasts (14, 29). Conversely, thromboxane A 2 (TXA 2 ) promotes fibroblast proliferation, increases pulmonary vascular permeability, and induces lung inflammation (18,21,24). Interestingly, a recent study has demonstrated that the decreased ratio of prostacyclin synthesis to thromboxane synthesis is associated with the development of pulmonary fibrosis (4).…”
mentioning
confidence: 99%
“…Besides thrombin, we also evaluated TNF-␣ with respect to lung edema formation in mice. No significant changes were observed up to 120 minutes duration of the experiment (10 ng/mL TNF-␣, data not shown), which is consistent with earlier reports from rats 43 and rabbits. 44 …”
Section: Pde2 Inhibition Reduces Wet-dry Weight Ratio and Lung Permeasupporting
confidence: 92%
“…In line with the notion that TNF-α cannot cause edema by itself, TNF-α failed to cause pulmonary edema in isolated perfused lungs within 1 hour [78,79] or 3 hours (own unpublished data). These findings are supported by the observation that in TNF-α perfused lungs antibodies in the perfusate did not reach the alveolar space and vice versa, indicating that the lung vascular barrier was intact [67].…”
Section: Platelet-activating Factor (Paf)supporting
confidence: 71%